2005
DOI: 10.1107/s0108270105007778
|View full text |Cite
|
Sign up to set email alerts
|

(E,E)-2,5-Dipropoxy-1,4-bis[2-(2,4,6-trimethoxyphenyl)ethenyl]benzene

Abstract: The title compound, C30H34O8, crystallizes in the space group P-1 with one-half of a molecule in the asymmetric unit. A three-dimensional network is generated by OCH3...pi and CH...pi interactions. The conformation of the C-C bond exocyclic to the central benzene ring is different from that of every other known derivative. A comparison of the geometry of the title molecule and of its solid-state structure with other 2,4,6-trimethoxy-substituted PPV [i.e. poly(p-phenylenevinylene)] oligomers, in particular the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…The choice of the [sp,sp] conformer is based on recent structural studies performed on compounds 4a, 4c, 4f, 4i, 4l, 5a and 7 which showed that this is the conformer also found in the crystal [13,[16][17][18]. Calculated geometries of the neutral forms of compounds 4a, 4b, 4c, 4h, 4k, 4l, 5a and 7 present no surprises.…”
Section: Theoretical Calculationsmentioning
confidence: 93%
“…The choice of the [sp,sp] conformer is based on recent structural studies performed on compounds 4a, 4c, 4f, 4i, 4l, 5a and 7 which showed that this is the conformer also found in the crystal [13,[16][17][18]. Calculated geometries of the neutral forms of compounds 4a, 4b, 4c, 4h, 4k, 4l, 5a and 7 present no surprises.…”
Section: Theoretical Calculationsmentioning
confidence: 93%
“…The parallel molecular packing is mainly attributed to the steric hindrance introduced by the thiomethyl and methoxyl units. The existence of strong OCH 3 ⋅⋅⋅ π interaction19 is evident from the close contact (2.682 Å) between the terminal hydrogen atom on the methoxyl group and the center of the middle ring in the neighboring molecule.…”
Section: Methodsmentioning
confidence: 99%
“…The solid-state structures and electronic properties of one particular class of these oligomeric organic semiconductors, viz. distyrylbenzenes, oligomeric derivatives of PPV [poly(pphenylene vinylene)], have already been extensively studied and the influence of substituents on the properties of the carbon backbone have been investigated (Baeke et al, 2007;Vande Velde et al, 2004;Vande Velde, Baeke et al 2005;Vande Velde, De Borger et al, 2005;Vande Velde et al, 2006;Irngartinger et al, 1994;Hakansson et al, 1992;Bartholomew et al, 2000a,b;Coates et al, 1998;Nohra et al, 2006;Renak et al, 1999;Sancho-Garcia et al, 2005;Zeller et al, 2005). However, keeping in mind the tunability of these materials, it is equally interesting to determine the effects of the replacement of the ethenylic -CH CH-link by other spacers such as -CH N-…”
Section: Commentmentioning
confidence: 99%